PENGARUH UTANG JANGKA PENDEK DAN UTANG JANGKA PANJANG TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH INDONESIA TAHUN 2016-2020 - Fira Gustira; Mellya Embun Baining; Novi Mubyarto (EKSYA : Jurnal Ekonomi Syariah, 2022)
This study aims to determine whether there is an influence between short-term debt and long-term debt on profitability at Indonesian Islamic Commercial Banks in 2016-2020. The population in this study is all Indonesian Islamic Commercial Banks. The data used is secondary data taken from the Financial Services Authority (OJK) in 2016-2020. The population in this study used the purposive sampling method at Indonesian Islamic Commercial Banks during the 2016-2020 period and based on predetermined criteria. The analytical method used is the multiple linear regression analysis method with the Eviews 10.0 application tool.The results based on the t test show that partially short-term debt has a negative but significant effect on profitability at Indonesian Islamic Commercial Banks in 2016-2020, and long-term debt variables have positive and insignificant effect on profitability at Indonesian Islamic Commercial Banks in 2016-2020. . Based on the F test simultaneously short-term debt and long-term debt have a positive and significant effect on profitability at Indonesian Islamic Commercial Banks in 2016-2020.